Peptide inhibitors of protein kinases - Discovery, characterisation and use - Marie A. Bogoyevitch (2018)
Protein kinases are now the second largest group of drug targets, and most protein kinase inhibitors in clinical development are directed towards the ATP-binding site. However, these inhibitors must compete with high intracellular ATP concentrations and they must discriminate between the ATP-binding sites of all protein kinases as well the other proteins that also utilise ATP. It would therefore be beneficial to target sites on protein kinases other than the ATP-binding site. This review describes the discovery, characterisation and use of peptide inhibitors of protein kinases. In many cases, the development of these peptides has resulted from an understanding of the specific protein-binding partners for a particular protein kinase. In addition, novel peptide sequences have been discovered in library screening approaches and have provided new leads in the discovery and/or design of peptide inhibitors of protein kinases. These approaches are therefore providing exciting new opportunities in the development of ATP non-competitive inhibitors of protein kinases. © 2005 Elsevier B.V. All rights reserved.